(untitled) (Entrepreneurship Journal for Finance and Business, 2024)
This study sheds light on new methods of dominating young people through the use of social media platforms such as Facebook, YouTube and other platforms to market audio clips that act as psychotropic drugs after getting used to listening to them, which then causes hallucinations and loss of psychological and physical balance, which requires enriching scientific knowledge about them, which opens the way for more research efforts, and proving its hypothesis that focuses on the importance of awareness and therapeutic tactics (such as the role of the family, school, and government agencies) in order to consolidate strategies to combat organized crime, which necessitated dismantling the nature of digital drugs and explaining their most important types and how to market them through the misuse of the GPL feature, and exposing their psychological, social, and technical causes and stating their psychological, social, economic, and sensory risks, then clarifying the most important solutions inherent in the tactics of reducing and limiting the drugs under study and their negative effects, so that the study comes out with a number of conclusions and recommendations, the most important of which is empowering legislative and judicial bodies and law enforcement with the necessary skills and tools to combat digital drug crimes effectively, as well as achieving balance The healthy balance between screen time and social time is compounded by the effort to create parent forums and online communities to share experiences and advice.